The monk's record player : Thomas Merton, Bob Dylan, and the perilous summer of 1966 - Hudson, Bob, 1953- (Grand Rapids : Eerdmans Publishing Co., 2018)
"In 1965 Thomas Merton fulfilled a twenty-four-year-old dream and went to live as a hermit beyond the walls of his Trappist monastery. Seven months later, after a secret romance with a woman half his age, he was in danger of losing it all. Yet on the very day that his abbot uncovered the affair, Merton found solace in an unlikely place--the songs of Bob Dylan, who, as fate would have it, was experiencing his own personal and creative crises during the summer of 1966"--Amazon.com.
Includes bibliographical references and index.
Print version record.
Added to collection customer.56279.3
Keywords: Merton, Thomas, -- 1915-1968.; Dylan, Bob, -- 1941- -- Influence; Baez, Joan; Baez, Joan; Dylan, Bob, -- 1941-; Merton, Thomas, -- 1915-1968.; Popular culture -- United States -- History -- 20th century; Influence (Literary, artistic, etc.); Popular culture; United States; RELIGION / Institutions & Organizations; History; Electronic books